1990
DOI: 10.1164/ajrccm/142.6_pt_1.1407
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Activated T Lymphocytes and Eosinophils in Bronchial Biopsies in Stable Atopic Asthma

Abstract: We have used immunohistochemistry and monoclonal antibodies to analyze the phenotypic composition and activation status of the cellular infiltrate of bronchial biopsies obtained by fiber optic bronchoscopy of 11 atopic asthmatic subjects (FEV1% predicted range 78 to 114), 9 atopic nonasthmatic control subjects, and 10 normal healthy subjects. Examination of mucosal biopsies obtained from both central (level I) and subsegmental (level II) bronchi showed that the highest number of CD45-, DC3-, DC4-, and CD8-posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
399
2
8

Year Published

1997
1997
2010
2010

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 836 publications
(425 citation statements)
references
References 3 publications
16
399
2
8
Order By: Relevance
“…In the case of allergic asthma, the airway wall is infiltrated by Th2 cells, eosinophils and mast cells, [28][29][30][31] and AHR is considered to be the result of a combination of submucosal edema, infiltration of the airway epithelium by eosinophils and lymphocytes, damage to epithelial cells, and direct effect of mediators derived from mast cells and eosinophils. The occurrence of these phenomena has been confirmed in murine models in which Th2-type immune responses were induced.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of allergic asthma, the airway wall is infiltrated by Th2 cells, eosinophils and mast cells, [28][29][30][31] and AHR is considered to be the result of a combination of submucosal edema, infiltration of the airway epithelium by eosinophils and lymphocytes, damage to epithelial cells, and direct effect of mediators derived from mast cells and eosinophils. The occurrence of these phenomena has been confirmed in murine models in which Th2-type immune responses were induced.…”
Section: Discussionmentioning
confidence: 99%
“…It is recognized that CD4 + T-helper type 2 (Th2) cells and their cytokines (interleukin (IL)-4, IL-5, and IL-13) are responsible for initiating and maintaining allergic disorders. 1,2 Numerous studies indicated that regulating asthma and allergic diseases is complex, involving several different mechanisms and cell types, and might not be reflected in a simple, dichotomous balance of polarized cells, as suggested by the T-helper type 1 (Th1)/Th2 paradigm. 3,4 Dendritic cells (DCs), as professional antigen-presenting cells, have an important function in antigen presentation in the airways, and the cytokine profile secreted by DCs can influence differentiation of T cells.…”
Section: Introductionmentioning
confidence: 99%
“…Asthma is characterised by a chronic inflammatory process, consisting of eosinophils, lymphocytes and macrophages together with bronchial hyper-responsiveness (BHR) (Azzawi et al, 1990;Bousquet et al, 1990;Djukanovic et al, 1990;Bradley et al, 1991). One of the consequences of chronic airway inflammation in asthma is remodelling of the airways, which consists of increases in airway smooth muscle (ASM) mass (Dunnill et al, 1969), goblet cell hyperplasia (Laitinen et al, 1985;Aikawa, 2001) and subepithelial fibrosis (Roche et al, 1989).…”
Section: Introductionmentioning
confidence: 99%